Becoming Resilient and Selfless: A Grounded Theory of Service despite the Threats during Pandemic - Friales, Wilter (JPAIR Multidisciplinary Research, 2021)
Frontliners were referred to the civil workers fighting against the pandemic, which includes the nurses, doctors, and other health workers and allied professionals; Officials and staff of the Inter-Agency Task Force on Emerging and Infectious Diseases (IATF); The uniformed personnel of the Armed Forces of the Philippines (AFP) and the Philippine National Police (PNP); Media; Various Government Agencies, Groceries, Banks, Food Establishments, and Delivery Services who ensure that basic services are provided to the people; Private sectors, Volunteers; and Civil society organizations. The study intends to explore the experiences of these Frontliners in doing their service to people despite the risks and threats to their lives. It used a grounded theory approach to generate themes, and themes emerge from the data drawn from varied situations and contexts to capture and explain the essence of meaning or experience of the Frontliners. As a result, categories and sub-categories had emerged from narratives of experiences of the Frontliners. Becoming resilient and selfless are two larger categories that transpired after all the categories and sub-categories were combined. Resilience and selflessness emerged as important attributes manifested by the Frontliners in doing service despite the pandemic threats.